Kantian Remorse with and without Self-Retribution. Issue 3 (24th September 2022) - Vilhauer, Benjamin
Abstract: Kant's account of the pain of remorse involves a hybrid justification based on self-retribution, but constrained by forward-looking principles which say we must channel remorse into improvement and moderate its pain to avoid damaging our rational agency. Kant's corpus also offers material for a revisionist but textually grounded alternative account based on wrongdoers' sympathy for the pain they cause. This account is based on the value of care, and has forward-looking constraints much like Kant's own account. Drawing on Kant's texts and recent work in empirical psychology, I argue that sympathetic remorse may fulfil Kant's forward-looking goals better than self-retributive remorse.